How to Increase Parental and Community Awareness in Education at SDN Glumpang Minyeuk: A Literature Review - Irmayani Irmayani (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This literature review explores strategies to enhance parental and community awareness of education at SDN Glumpang Minyeuk. The study highlights the significance of active parental involvement and community engagement in fostering a supportive educational environment. Through an analysis of existing research, the review identifies key initiatives, including workshops for parents, collaborative programs with local organizations, and effective communication channels, to bolster awareness and participation in education. Furthermore, it discusses the role of technology in bridging gaps between schools and families, facilitating access to educational resources and information. The findings emphasize the need for ongoing efforts to cultivate a culture of learning and cooperation among parents, educators, and the wider community, ultimately contributing to improved educational outcomes for students.